The influence of politicians' sex on political budget cycles: An empirical analysis of Spanish municipalities - Israel García; Bernd Hayo (Philipps-University Marburg, School of Business and Economics, 2022)
Employing a sample of Spanish municipalities from the Madrid region for the period 2010-2019, we study the influence of a politician's sex on political budget cycles (PBCs). The Madrid region is subject to a homogenous set of budget rules, which allows consistently categorising budget expenditure items as either 'mandatory' or 'non-mandatory' public services. Differentiating between four sizes of municipalities, the gender influence is studied along two dimensions: mayor's sex and share of women in government. Except for the largest municipalities, we discover significant evidence of PBC-related changes, ranging between 3% and 7% of average municipal budgets, in mandatory spending for both sexes. The impact is roughly twice as large in the long term. On average, male and female mayors tend to increase pre-electoral mandatory spending, even when the government is gender balanced. However, in the (rare) case of female-dominated governments, mayors do not appear to engage in PBC-related activities, and may even decrease mandatory spending, before an election.
Keywords: C23; E62; D72; H72; J16; 330; Gender; Political budget cycles; Signalling mechanism; Local politicians; Fiscal policy; Spanish municipalities; Madrid region